Determinants of cost management in Micro and Small Enterprises (Revista Brasileira de Contabilidade e Gestão, 2022)
Objective: The objective of this research was to highlight the determinants of cost management in micro and small enterprises (MSE) in the city of Mossoró, state of Rio Grande do Norte, Brazil. Method: MSE are essential institutions for the Brazilian economy due to their representativeness in number of companies and for the generation of employment and income. To achieve the objective proposed in this study, a survey was carried out with a quantitative approach, by applying a questionnaire to managers of MSE. Results: We verified that cost management offers subsidies that assist in the managers’ decision-making, being inventory control and valuation, as well as increase in competitiveness, the determinants of cost management. The participants consider cost control information relevant for the planning and performance analysis of the company. Moreover, we found that the level of use of cost management in this research exceeded the average of Sebrae, which points out that 60% of companies do not use cost control, whereas in this research only 30% reported not to use it. Contributions: The research contributes to show the relevance of determinants for the MSE to carry out an effective cost management, indicating a list of practices adopted in the surveyed companies, which can serve as a guide for other companies to use in their decisions. Our results were convergent in some aspects and divergent in others with regard to empirical studies researched in the literature.
Keywords: employment and income generation; brazilian economy; micro and small companies; cost determinants; costs management